Multi-Omics Analysis Reveals the Systematic Relationship Between Oral Homeostasis and Chronic Sleep Deprivation in Rats - Chen, Pan; Wu, Hao; Yao, Hongliang; Zhang, Jiashuo; Fan, Weiyang; Chen, Zhen; Su, Weiwei; Wang, Yonggang; Li, Peibo (Frontiers in Immunology, 2022)
Sleep disorders were associated with oral health. Inflammation has especially been thought to be a key factor in linking oral diseases and sleep deficiency. However, how chronic sleep deprivation (CSD) affects oral homeostasis, particularly oral inflammation and oral microbiota, is still unknown. This study aimed to uncover the systematic relationship between oral homeostasis and CSD in rats. The metabolomics in serum, proteomics in the tongue tissues, and microbiome analysis in the oral cavity in CSD rats were performed. Multi-omics data integration analysis was performed to uncover the systematic relationship between oral homeostasis and CSD through the weighted correlation network analysis. We found that CSD could lead to oral inflammation in rats. CSD significantly increased systemic inflammation by enhancing the serum levels of IL-1β, IL-6 and inhibiting the serum level of IL-10. Serum levels of adrenocorticotropin hormone, corticosterone, and triiodothyronine were increased in CSD rats, and the steroid hormone biosynthesis pathway was also found to be involved in the perturbation resulting from CSD, together suggesting the activation of the hypothalamic-pituitary-adrenocortical and hypothalamic‐pituitary‐thyroid axis. CSD led to changes of oral microbiota composition, and g_Acinetobacter, Candidatus Chryseobacterium massiliae, and g_Moraxella were significantly correlated with multiple proteins in bacterial invasion of epithelial cells pathway, which may partially responsible for oral inflammation resulting from CSD. The changes of proteomic profiling expression caused by CSD in tongue tissues were mainly enriched in neurodegenerative diseases pathways and immune/inflammation-related pathways. Multi-omics analysis indicated that the inflammatory response-related modules were significantly correlated with the neurodegenerative disease-related module suggesting a possible link between neurodegenerative diseases and oral inflammation. Together, CSD induced oral inflammation and subtle changes on oral microbiota. Our study is helpful to further understand the role that oral homeostasis plays in the process by which CSD affects human health and disease.